Analysis of monosomy‐3 in immunomagnetically isolated circulating melanoma cells in uveal melanoma patients. (September 2016) - Tura, Aysegül; Merz, Hartmut; Reinsberg, Mihaela; Lüke, Matthias; Jager, Martine J.; Grisanti, Salvatore; Lüke, Julia
Summary: Monosomy‐3 in primary uveal melanoma (UM) is associated with a high risk of metastasis and mortality. Although circulating melanoma cells (CMC) can be found in most UM patients, only approximately 50% of the patients develop metastases. We utilized a novel immuno‐FISH assay to detect chromosome‐3 in intact CMC isolated by dual immunomagnetic enrichment. Circulating melanoma cells were detected in 91% of the patients (n = 44) with primary non‐metastatic UM, of which 58% were positive for monosomy‐3. The monosomy‐3 status of CMC corresponded to the monosomy‐3 status of the primary tumor in 10 of the 11 patients where this could be tested. Monosomy‐3 in the CMC was associated with an advanced tumor stage (P = 0.046) and was detected in all four patients who developed metastasis within the follow‐up period of 4 yr. This non‐invasive technique may enable the identification of UM patients at risk for metastasis particularly when a primary tumor specimen is unavailable.